الديمقراطية في العالم العربي: ضرورة التغيير - صاهد, فاطمة الزهراء (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
Democracy exercise in Arab societies is taking a different shape from occidental conception that has imposed a particular style or pattern of democratie governance centered on human rights and liberality and according to some known major elements, these latter are unfortunately unavailable in the majority, if not, in all Arab regimes. Thus, the basic problems are that Arab regimes lack democracy culture and are still violating human rights. More than this, these regimes express no will to fulfill conditions permitting the promotion of these rights as a social reality daily perceived by the population and the case concerns even those supposedly democratic countries where foundations democracy are still weak. Within this context, the transitions, mutations and the different metamorphosis prevailing in Arab countries are generally associated with what is called "Arab Spring", a relation resulting from the bankruptcy of typical, political discourse that failed in achieving people’s objectives and goals. Such metamorphosis, even associated with Arab spring, still constitute a source of motivation for the popular movement which is calling for a rational political systems able to make required and expected changes in Arab societies, a simple conclusion that make us expose the following problematic: Regarding the actual situation, is there an Arab country ready for democratic changes?